The Slavic Miracles of the Great Martyr Saint Menas by Timothy of Alexandria - Stradomski, Jan (Vox Patrum, 2025)
The complete Slavic cycle of miracles of St Menas, consisting of a prologue and 13 miracles, is based on the edition of the Great Reader Mineia of the Moscow Metropolitan Makary. The text largely corresponds to the Greek version from Ivan Pomyalovsky’s 1900 edition, making it a valuable resource for understanding the Greek tradition as well. The Slavic text has been compared with other manuscripts containing the full cycle of miracles and following the same translation (B).